(3HdhZ efi GdLfGfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3LGSf Hf eMeO QVG, hdO GdeUfas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj CfRd GdcJGH Ydi YHOg HTjQG hfPjQG (B... (3bhdg GdMeO ddg, GdKfGA dg Ydi eG CfYe Hg YdjfG, bhdg QH GdYGdejf, eGdc GdLeGYGJs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg QH GdfGS(B: (3NGdbge, bhdg(B: (3edc GdfGS, SjOge, bhdg(B: (3GdhShGS(B: (3GdehShS, bhdg(B: (3GdNfGS, GSe ddTjWGf, jdbj GdhShSI aj UOhQ GdfGS, bhdg ef GdLfI, GdLf, bhdg(B: (3hGdfS, Hfj BOes
(3efbhdI Yf fSNI GdeDda, GdJj CJe JCdjagG SfI (B1335(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B3: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJaSjQ hYdhe GdbQBfs